Western Austronesian Applicative Constructions : Continuity and Change in Form and Meaning - Truong, Christina L., (Endangered and Lesser-Studied Languages and Dialects ;, 2025)
Applicative constructions are a distinctive grammatical feature of the Austronesian languages of western Indonesia, Malaysia, Singapore, and Brunei. Applicatives in these languages show varied syntactic and semantic properties, and are closely connected to causativization, aspectual meanings, and symmetrical voice. As a result, they do not fit neatly into 'canonincal' patterns for applicatives. This book adopts a construction-based, typologically-grounded approach, treating applicatives as pairings of form and meaning. Data from 85 languages is analyzed systematically, combining careful description with quantitative methods and extensive use of geomapping to explore the diverse properties of applicatives in this region and their diachronic development